Does the Choice of Well-Being Measure Matter Empirically? An Illustration with German Data - Koen Decancq; Dirk Neumann (Institute for the Study of Labor (IZA), 2014)
We discuss and compare five measures of individual well-being, namely income, an objective composite well-being index, a measure of subjective well-being, equivalent income, and a well-being measure based on the von Neumann-Morgenstern utilities of the individuals. After examining the information requirements of these measures, we illustrate their implementation using data from the German Socio-Economic Panel (SOEP) for 2010. We find sizeable differences in the characteristics of the individuals identified as worst off according to the different well-being measures. Less than 1% of the individuals belong to the bottom decile according to all five measures. Moreover, the measures lead to considerably different well-being rankings of the individuals. These findings highlight the importance of the choice of well-being measure for policy making.
Keywords: D31; D63; I30; 330; von Neumann-Morgenstern utility function; equivalent income; life satisfaction; composite well-being index; income; worst off; Germany